Semantic Density and Gravity in Lay-oriented Medical Knowledge Communication: The Case of the EPAR Summary for the Public - Hill-Madsen, Aage (Nordic Journal of English Studies, 2022)
<span style="color: rgba(0, 0, 0, 0.84); font-family: 'Noto Sans', 'Noto Kufi Arabic', -apple-system, 'system-ui', 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This article explores a particular medico-pharmaceutical genre called the <em style="box-sizing: border-box; color: rgba(0, 0, 0, 0.84); font-family: 'Noto Sans', 'Noto Kufi Arabic', -apple-system, 'system-ui', 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">European Assessment Report (EPAR) summary for the public<span style="color: rgba(0, 0, 0, 0.84); font-family: 'Noto Sans', 'Noto Kufi Arabic', -apple-system, 'system-ui', 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">, aimed at a lay readership. The texts provide general information about specific medicinal products and report the outcome of clinical trials preceding the products' marketing authorization in the EU. The aim of this study is to explore the character of the knowledge mediation taking place in the genre, with a specific focus on comprehensibility for lay readers. For analytical methodology, a framework derived from so-called Legitimation Code Theory has been adopted. The framework gauges <em style="box-sizing: border-box; color: rgba(0, 0, 0, 0.84); font-family: 'Noto Sans', 'Noto Kufi Arabic', -apple-system, 'system-ui', 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">semantic density<span style="color: rgba(0, 0, 0, 0.84); font-family: 'Noto Sans', 'Noto Kufi Arabic', -apple-system, 'system-ui', 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;"> (how much meaning is ‘condensed’ into a text) and <em style="box-sizing: border-box; color: rgba(0, 0, 0, 0.84); font-family: 'Noto Sans', 'Noto Kufi Arabic', -apple-system, 'system-ui', 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">semantic gravity <span style="color: rgba(0, 0, 0, 0.84); font-family: 'Noto Sans', 'Noto Kufi Arabic', -apple-system, 'system-ui', 'Segoe UI', Roboto, Oxygen-Sans, Ubuntu, Cantarell, 'Helvetica Neue', sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">(a text’s degree of abstractness/concreteness). The study assumes that high semantic density and a high degree of abstractness may be challenging to some reader groups. Analytical results reveal an overall degree of semantic density that is lower than that of scientific texts, but markedly higher than in non-specialized, everyday discourse. Moreover, across the texts, results reveal marked oscillation in the semantic density of individual words, reflecting what is in effect a fusion of two different registers belonging to very different levels of specialization. In terms of semantic gravity, findings indicate a maximum of abstractness in large parts of the texts. Altogether, the analyses reveal a clear affinity with textbooks that serve to initiate novices into the specialized conceptual ‘landscape’ of a given field of knowledge. The study ventures the hypothesis that this ‘textbook’ quality may be one of the most significant obstacles for certain reader groups.